Preparation method of environment-friendly, low odor water-based acrylic modified epoxy resin anticorrosive paint
Patent Information
- Application Number
- CN202411028203.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-30
AI Technical Summary
但是上述涂料中添加了大量的三聚磷酸铝作为防锈颜料,其虽然具有很好的防锈性能,但是其微溶于水,水解性差,三聚磷酸根离子解离速度慢,不能很好的克服闪锈的问题
[0031]本发明提供了一种环保低气味水性改性环氧树脂防腐涂料,采用接枝共聚合方法,引入丙烯酸酯链段改性环氧树脂,提高了树脂的玻璃化转变温度,特别是在涂料成膜后,在水性催干剂和氧气作用下,环氧树脂的双键发生氧化交联反应,形成网状结构,可以极大地提升漆膜的干燥速度、耐水性和耐腐蚀性。而且本发明在制备水性改性环氧树脂分散体中未添加高挥发速率、味道大的快干醇类溶剂,气味得到明显改善,丙烯酸聚合物的亲水部分提供混合树脂的水分散性。
Smart Images

Figure BDA0004969175980000171 
Figure BDA0004969175980000181 
Figure BDA0004969175980000191
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating. Background Technology
[0002] Automotive components such as drive shafts, brake drums, axles, leaf springs, shock absorbers, suspension assemblies, and chassis are among the most important parts of a car. Connected to the chassis and body via the transmission and braking systems, these components, being vital and closest to the ground, endure the harshest environmental conditions. They must possess excellent tensile strength, bending strength, and hardness. In humid environments or where corrosive media are present, they are prone to rust. The quality of the protective coating not only affects the overall aesthetics of the chassis system but also the vehicle's safety performance. Therefore, automotive components must undergo rigorous coating and anti-corrosion treatment during production to maintain vehicle safety and durability. Inadequate anti-corrosion treatment of automotive components can lead to performance degradation or structural damage, with potentially disastrous consequences.
[0003] With increasingly stringent environmental requirements for industrial coatings, the use of water-based coatings with low volatile organic compounds (VOCs) and high corrosion resistance has become inevitable. The excessive use of solvent-based coatings has led to a significant generation of VOCs, making the reduction of their production and use a nationwide task. Water-based coatings, compared to solvent-based coatings, have a clear advantage in both environmental friendliness and health benefits, making them the most effective way to reduce VOC emissions from coatings and achieve source reduction. Replacing traditional VOC solvents with ordinary purified water in coatings can simultaneously improve two important indicators: environmental emissions and increased coating utilization. This not only reduces costs but also decreases hazardous waste generation, lowers production safety risks, optimizes the working environment for workers, reduces fuel consumption, and increases output and production efficiency, achieving a win-win situation for both economic and environmental benefits. Patent application number 201710588630.9 provides a water-based anti-corrosion coating for automotive parts and its preparation method, comprising the following raw materials in parts by weight: 1-5 parts of nano-slurry, 25-29 parts of water-based modified alkyd resin, 1-2 parts of dimethylethanolamine, 11-20 parts of aluminum tripolyphosphate, 8-7 parts of calcium carbonate, 25-38 parts of deionized water, 1.3-2.8 parts of defoamer, 2-2.5 parts of dispersant, and 1-2 parts of corrosion inhibitor. The nano-slurry contains nano-titanium dioxide and nano-zinc oxide. The coating uses organosilicon polyurethane composite modified alkyd resin to improve the anti-aging performance of the coating, and adds nano-slurry composed of nano-titanium dioxide and nano-zinc oxide to improve the anti-ultraviolet radiation performance of the coating. It has the advantages of high hardness, good flexibility, and good water resistance. However, the aforementioned coatings contain a large amount of aluminum tripolyphosphate as an anti-rust pigment. While it has excellent anti-rust properties, it is only slightly soluble in water, has poor hydrolysis, and the tripolyphosphate ion dissociation rate is slow, thus failing to effectively overcome the problem of flash rust. Based on these issues, it is necessary to provide an environmentally friendly, low-odor, and highly corrosion-resistant water-based coating. Summary of the Invention
[0004] The technical problem to be solved by this invention is to provide an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating method to address the shortcomings of existing technologies. This invention uses glycidyl methacrylate to modify epoxy resin, and then uses acrylate monomers and acrylic monomers to further modify it, obtaining a waterborne modified epoxy resin dispersion with good dispersibility. Then, it is used as the main film-forming substance, and a certain amount of modified graphene / titanium dioxide material is added for further modification. The resulting coating not only has good adhesion to the substrate, but also excellent water resistance and corrosion resistance.
[0005] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows:
[0006] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0007] (1) Preparation of waterborne modified epoxy resin dispersion:
[0008] Epoxy resin, fatty acid, and modified monomers are added to a first solvent for esterification reaction. Then, a crosslinking agent is added, followed by the addition of a mixture of acrylate monomers, styrene monomers, a second solvent, and an initiator to the reaction system. The reaction is carried out under heat for one incubation period, followed by the addition of an acrylate monomer solution and another incubation period. After the reaction is completed, an amine neutralizer is added for neutralization, and then deionized water is added to adjust the solid content to obtain an aqueous modified epoxy resin dispersion.
[0009] (2) Preparation of modified graphene / titanium dioxide materials:
[0010] Graphene oxide, titanium dioxide, and silane coupling agent were added to N,N-dimethylformamide and ultrasonically dispersed until uniform. Then, 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC) was added and stirred to mix. L-histidine solution was then added and stirred to react. After the reaction was completed, the pH of the reaction system was adjusted. Tannic acid was then added to the reaction system and the temperature was raised to react. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the precipitate was washed and freeze-dried to obtain the modified graphene / titanium dioxide material.
[0011] (3) Preparation of color paste:
[0012] Add some deionized water to the mixing container, then add water-based wetting and dispersing agent, water-based defoamer, and water-based wetting agent under stirring conditions, and carry out one stirring and dispersion. Then add the remaining deionized water, modified graphene / titanium dioxide material, pigments and fillers under stirring conditions, and carry out a second stirring and dispersion. Finally, grind the mixed slurry to obtain a color paste.
[0013] (4) Preparation of anti-corrosion coatings:
[0014] Add water-based modified epoxy resin dispersion to a mixing container, and under stirring conditions add amine neutralizer, water-based drier, water-based coupling agent, water-based film-forming aid, color paste, water-based flash rust inhibitor, and water-based thickener, and stir and disperse to obtain an environmentally friendly, low-odor water-based acrylic modified epoxy resin anti-corrosion coating.
[0015] Preferably, in step (1), the epoxy resin is a bisphenol A type epoxy resin; and / or the first solvent and the second solvent are one or a mixture of two of propylene glycol methyl ether and ethylene glycol tert-butyl ether; and / or the modified monomer is glycidyl methacrylate; and / or the crosslinking agent is hydroxymethylacrylamide; and / or the acrylate monomer is methyl methacrylate; and / or the initiator is benzoyl peroxide; and / or the acrylic monomer is acrylic acid; and / or the amine neutralizing agent is dimethylethanolamine.
[0016] Preferably, in step (1), the amounts of epoxy resin, fatty acid, first solvent, crosslinking agent, acrylate monomer, styrene monomer, second solvent, initiator, acrylate monomer solution, and amine neutralizer are 10-15 wt%, 8-10 wt%, 5-8 wt%, 1-3 wt%, 5-8 wt%, 1-5 wt%, 7-10 wt%, 0.5-1.5 wt%, 11-15 wt%, and 1-3 wt% of the mass of the waterborne modified epoxy resin dispersion, respectively. Further, the solid content of the waterborne modified epoxy resin dispersion is 45-48 wt%.
[0017] Preferably, in step (1), the esterification reaction is carried out at a temperature of 200-250°C for 1-2 hours; and / or the crosslinking agent is added at a temperature of 120-140°C; and / or the mixture of acrylate monomers, styrene monomers, the second solvent, and the initiator is added dropwise over a period of 2-4 hours; and / or the first heat preservation reaction is carried out at a temperature of 120-140°C for 1-2 hours; and / or the acrylate monomer solution is added dropwise over a period of 1-2 hours; and / or the second heat preservation reaction is carried out over a period of 1-2 hours.
[0018] Preferably, in step (2), the mass ratio of graphene oxide, titanium dioxide, and silane coupling agent is (0.3-0.5):1:(0.003-0.006).
[0019] Preferably, in step (2), the ultrasonic power of ultrasonic dispersion is 100-150W and the ultrasonic time is 1-2h.
[0020] Preferably, in step (2), the amount of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide added is 20-30% of the mass of graphene oxide; the stirring speed during mixing is 300-500 rpm, and the mixing time is 20-30 min.
[0021] Preferably, in step (2), the amount of L-histidine added is 20-30% of the mass of graphene oxide.
[0022] Preferably, in step (2), the temperature of the stirring reaction is room temperature, the stirring speed is 200-500 rpm, and the time is 20-30 h.
[0023] Preferably, in step (2), the pH of the reaction system is adjusted to 10, the mass ratio of tannic acid to graphene oxide is 1:(1-2), the temperature of the reaction is raised to 75-85℃, the stirring speed during the reaction is 200-500rpm, and the reaction time is 5-7h.
[0024] Preferably, in step (3), the pigments and fillers are one or more mixtures of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, fumed nano silica, talc, iron oxide red, and polyamide wax.
[0025] Preferably, in step (3), the pigment and filler are a mixture of zinc strontium phosphate anti-rust pigment, high gloss barium sulfate, high pigment carbon black, and fumed nano silica, and the mass ratio of zinc strontium phosphate anti-rust pigment, high gloss barium sulfate, high pigment carbon black, and fumed nano silica is (3-5):(8-10):(2-3):(1-2).
[0026] Preferably, in step (3), the pigment and filler are a mixture of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, fumed nano silica, talc, iron oxide red, and polyamide wax; the mass ratio of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, talc, iron oxide red, fumed nano silica, and polyamide wax is (3-5):(10-15):(5-10):(5-7):(1-2):(1-2).
[0027] Preferably, in step (3), the amounts of deionized water, waterborne defoamer, waterborne wetting and dispersing agent, waterborne wetting agent, pigments and fillers, and modified graphene / titanium dioxide material are 12-15 wt%, 0.1-0.2 wt%, 3-5 wt%, 0.2-0.5 wt%, 10-45 wt%, and 4-8 wt% of the mass of the waterborne modified epoxy resin dispersion, respectively.
[0028] Preferably, in step (4), the amount of waterborne modified epoxy resin dispersion added is 40-70 wt% of the total amount of environmentally friendly, low-odor waterborne acrylic modified epoxy resin anticorrosive coating. The amounts of amine neutralizer, waterborne drying agent, waterborne film-forming aid, waterborne coupling agent, waterborne anti-flash rust agent, and waterborne thickener are 1-5 wt%, 3-5 wt%, 3-6 wt%, 0.2-2 wt%, 1-3 wt%, and 1-2 wt% of the mass of waterborne modified epoxy resin dispersion, respectively.
[0029] Preferably, the fatty acids in this invention are long-chain fatty acids or unsaturated fatty acids.
[0030] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0031] This invention provides an environmentally friendly, low-odor waterborne modified epoxy resin anticorrosive coating. It employs a graft copolymerization method to introduce acrylate segments to modify the epoxy resin, thereby increasing the resin's glass transition temperature. Particularly after film formation, under the action of a waterborne drier and oxygen, the double bonds of the epoxy resin undergo an oxidative cross-linking reaction, forming a network structure. This significantly improves the drying speed, water resistance, and corrosion resistance of the paint film. Furthermore, this invention avoids the addition of high-volatility, odor-laden, fast-drying alcohol solvents in the preparation of the waterborne modified epoxy resin dispersion, resulting in a significantly improved odor. The hydrophilic portion of the acrylic polymer provides water dispersibility for the mixed resin.
[0032] This invention uses a water-based modified epoxy resin dispersion as the main film-forming material, and further combines it with deionized water, amine neutralizer, water-based drier, water-based defoamer, water-based wetting agent, water-based wetting and dispersing agent, pigments and fillers, modified graphene / titanium dioxide material, water-based coupling agent, water-based film-forming aid, water-based flash rust inhibitor, and water-based thickener to prepare a water-based modified epoxy resin anti-corrosion coating. It is applied to the anti-corrosion coating of automotive parts, such as drive shafts, brake drums, axles, leaf springs, shock absorbers, suspension assemblies, chassis, etc., realizing the water-based coating of automotive parts. The coating provided by this invention has low odor, fast drying speed, and excellent film adhesion, water resistance, salt spray resistance, excellent outdoor weather resistance, good gloss and color retention, good flexibility, and good hardness. It improves upon the shortcomings of conventional water-based epoxy ester resin coatings, such as slow drying speed, strong odor, low hardness, and poor weather resistance. It is suitable for coating scenarios in professional anti-corrosion coating production lines for automotive parts, greatly improving the coating production efficiency of automotive parts factories, providing excellent protection for various automotive parts, reducing hazardous waste generation, lowering production safety risks, optimizing the working environment for workers, reducing fuel and energy consumption, increasing output and production efficiency, achieving a win-win situation for economic and environmental benefits, and accelerating the industrialization and market share of water-based coatings for automotive parts in my country.
[0033] This invention incorporates a modified graphene / titanium dioxide material. Titanium dioxide is dispersed between the graphene layers, and L-histidine is grafted onto the surface, further increasing the interlayer spacing of the graphene and preventing material aggregation. The resulting modified graphene / titanium dioxide material exhibits excellent dispersibility. The modified graphene / titanium dioxide material of this invention has a layered structure, possessing certain barrier properties. It can fill the microporous structure of the coating matrix and increase the diffusion path length of corrosive media through the coating matrix, thereby forming a labyrinth effect and improving the corrosion resistance of the coating. Furthermore, the L-histidine on the modified graphene / titanium dioxide material can act as a corrosion inhibitor, forming an oxide passivation layer with the matrix, thus better protecting the matrix. Detailed Implementation
[0034] To better understand the above-mentioned objectives, features, and advantages of the present invention, the solutions of the present invention will be further described below. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
[0035] Many specific details are set forth in the following description in order to provide a full understanding of the invention, but the invention may also be practiced in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of the invention, and not all embodiments.
[0036] This invention provides a method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating, comprising the following steps:
[0037] (1) Preparation of waterborne modified epoxy resin dispersion:
[0038] Epoxy resin, fatty acid, and modified monomers are added to the first solvent for esterification reaction. Then, a crosslinking agent is added for crosslinking. Next, a mixture of acrylate monomers, styrene monomers, a second solvent, and an initiator is added to the reaction system. The reaction is carried out at a constant temperature for one time. Then, an acrylate monomer solution is added, and the reaction is carried out at a constant temperature for another time. After the reaction is completed, an amine neutralizer is added for neutralization. Finally, deionized water is added to adjust the solid content to obtain an aqueous resin dispersion.
[0039] (2) Preparation of modified graphene / titanium dioxide materials:
[0040] Graphene oxide, titanium dioxide, and silane coupling agent were added to N,N-dimethylformamide and ultrasonically dispersed evenly. Then, 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide was added and stirred to mix. Then, L-histidine solution was added and stirred to react. After the reaction was completed, the pH of the reaction system was adjusted. Then, tannic acid was added to the reaction system and the temperature was raised to react. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the precipitate was washed and freeze-dried to obtain the modified graphene / titanium dioxide material.
[0041] (3) Preparation of color paste:
[0042] Add some deionized water to the mixing container, then add water-based wetting and dispersing agent, water-based defoamer, and water-based wetting agent under stirring conditions, and carry out one stirring and dispersion. Then add the remaining deionized water, modified graphene / titanium dioxide material, pigments and fillers under stirring conditions, and carry out a second stirring and dispersion. Finally, grind the mixed slurry to obtain a color paste.
[0043] (4) Preparation of anti-corrosion coatings:
[0044] Add water-based modified epoxy resin dispersion to a mixing container, and under stirring conditions add amine neutralizer, water-based drier, water-based coupling agent, water-based film-forming aid, color paste, water-based anti-flash rust agent, and water-based thickener, and stir and disperse to obtain an environmentally friendly, low-odor water-based acrylic modified epoxy resin anti-corrosion coating.
[0045] Regarding step (1):
[0046] In some embodiments, the epoxy resin is a bisphenol A type epoxy resin; and / or the first solvent and the second solvent are one or a mixture of two of propylene glycol methyl ether and ethylene glycol tert-butyl ether; and / or the modifying monomer is glycidyl methacrylate; and / or the crosslinking agent is hydroxymethylacrylamide; and / or the acrylate monomer is methyl methacrylate; and / or the initiator is benzoyl peroxide; and / or the acrylic monomer is acrylic acid; and / or the amine neutralizing agent is dimethylethanolamine.
[0047] The solvent of this invention exhibits excellent solubility for epoxy resins, acrylate monomers, modified monomers, and acrylic monomers, and has a low odor. This invention uses glycidyl methacrylate as a modified monomer to introduce acrylate segments onto the epoxy resin molecule, thereby increasing the glass transition temperature of the resin. This invention also utilizes graft copolymerization to introduce hydrophilic hydroxymethylacrylamide groups into the resin, forming a cross-linked structure, and then improves the resin's hydrophilicity through modification with methyl methacrylate and acrylic monomers.
[0048] In some embodiments, the initiator may be benzoyl peroxide; and / or the amine neutralizer may be dimethylethanolamine; and / or the concentration of the acrylic monomer solution may be 50-91 wt%. The present invention uses dimethylethanolamine as an amine neutralizer, which has advantages such as low odor compared to other amine neutralizers.
[0049] In some embodiments, the amounts of the epoxy resin, fatty acid, first solvent, crosslinking agent, acrylate monomer, styrene monomer, second solvent, initiator, acrylate monomer solution, and amine neutralizer are 10-15 wt%, 8-10 wt%, 5-8 wt%, 1-3 wt%, 5-8 wt%, 1-5 wt%, 7-10 wt%, 0.5-1.5 wt%, 11-15 wt%, and 1-3 wt% of the mass of the waterborne modified epoxy resin dispersion, respectively. Further, the solid content of the waterborne modified dispersion is 45-48 wt%.
[0050] In some embodiments, the esterification reaction is carried out at a temperature of 200-250°C for 1-2 hours; and / or the temperature at which the crosslinking agent is added is 120-140°C; and / or the mixture of acrylate monomers, styrene monomers, the second solvent, and the initiator is added dropwise over 2-4 hours; and / or the temperature of the first heat treatment is 120-140°C for 1-2 hours; and / or the acrylic monomer solution is added dropwise over 1-2 hours; and / or the heat treatment time for the second heat treatment is 1-2 hours.
[0051] Regarding step (2):
[0052] In some embodiments, the mass ratio of graphene oxide, titanium dioxide, and silane coupling agent is (0.3-0.5):1:(0.003-0.006).
[0053] In some embodiments, the ultrasonic power for ultrasonic dispersion is 100-150W, and the ultrasonic time is 1-2h.
[0054] In some embodiments, the amount of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide added is 20-30% of the mass of graphene oxide; the stirring speed during mixing is 300-500 rpm, and the mixing time is 20-30 min.
[0055] In some embodiments, the amount of L-histidine added is 20-30% of the mass of graphene oxide.
[0056] In some embodiments, the stirring reaction is carried out at room temperature, at a stirring speed of 200-500 rpm, and for a time of 20-30 h.
[0057] In some embodiments, the pH of the reaction system is adjusted to 10, the mass ratio of tannic acid to graphene oxide is 1:(1-2), the temperature of the reaction is raised to 75-85℃, the stirring speed during the reaction is 200-500 rpm, and the reaction time is 5-7h.
[0058] Under ultrasonic conditions, this invention uses a silane coupling agent to modify a mixture of graphene oxide and titanium dioxide. Under ultrasonic conditions, titanium dioxide penetrates into the interlayers of graphene oxide, and the silane coupling agent completes the modification through chemical bonding or physical adsorption with titanium dioxide and graphene oxide, thereby improving the interfacial properties of graphene oxide and titanium dioxide. This invention also uses EDC as a grafting coupling agent to graft L-histidine onto the silane coupling agent-modified graphene oxide / titanium dioxide surface, followed by reduction with tannic acid, thus obtaining a modified graphene oxide / titanium dioxide material. The corrosion-inhibiting effects of tannic acid and L-histidine, along with the electron-blocking effect of the modified graphene / titanium dioxide material, work synergistically to provide corrosion protection.
[0059] Regarding step (3):
[0060] In some embodiments, the pigments and fillers are one or more mixtures of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, fumed nano silica, talc, ferrous oxide red, and polyamide wax.
[0061] In some embodiments, in step (3), the pigments and fillers are a mixture of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, and fumed nano silica, and the mass ratio of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, and fumed nano silica is (3-5):(8-10):(2-3):(1-2).
[0062] In some embodiments, in step (3), the pigment and filler are a mixture of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, fumed nano silica, talc, iron oxide red, and polyamide wax; the mass ratio of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, talc, iron oxide red, fumed nano silica, and polyamide wax is (3-5):(10-15):(5-10):(5-7):(1-2):(1-2).
[0063] In some embodiments, in step (3), the amounts of deionized water, aqueous defoamer, aqueous wetting and dispersing agent, aqueous wetting agent, pigments and fillers, and modified graphene / titanium dioxide material are 12-15 wt%, 0.1-0.2 wt%, 3-5 wt%, 0.2-0.5 wt%, 10-45 wt%, and 4-8 wt% of the mass of the aqueous modified epoxy resin dispersion, respectively.
[0064] This invention adds zinc strontium phosphate anti-rust pigment to the coating matrix. The synergistic effect of zinc phosphate, ZMP, RZ and other components enhances the polarization resistance of the steel surface and provides an adhesive corrosion inhibitory effect. The protective film composed of the complex achieves anodic protection and improves the corrosion resistance of the substrate.
[0065] Regarding step (4):
[0066] In some embodiments, in step (4), the amount of waterborne modified epoxy resin dispersion added is 40-70 wt% of the total amount of environmentally friendly, low-odor waterborne acrylic modified epoxy resin anticorrosive coating. The amounts of amine neutralizer, waterborne drying agent, waterborne film-forming aid, waterborne coupling agent, waterborne anti-flash rust agent, and waterborne thickener are 1-5 wt%, 3-5 wt%, 3-6 wt%, 0.2-2 wt%, 1-3 wt%, and 1-2 wt% of the mass of waterborne modified epoxy resin dispersion, respectively.
[0067] Furthermore, in this invention, the aqueous coupling agent is an aqueous silane coupling agent, the aqueous flash rust inhibitor is an oxidation film-forming type flash rust inhibitor, the aqueous thickener is an aqueous polyurethane associative type thickener, and the aqueous wetting agent is a siloxane-type twin structure surfactant.
[0068] The water-based drying agent used in this invention has excellent storage stability, low odor, high efficiency and non-toxicity, and strong oxidative polymerization drying activity, which can rapidly dry the paint film and significantly improve the drying properties, hardness, adhesion and water resistance of the paint film. The water-based coupling agent uses a water-based silane coupling agent, which generates silanol through the hydrolysis of silane groups and undergoes a condensation reaction with residual moisture on the substrate, thereby achieving chemical anchoring of the coupling agent molecules with the substrate, ultimately improving the adhesion and density of the paint film to the substrate. The water-based flash rust inhibitor is an oxidative film-forming type flash rust inhibitor that can prevent cathodic reactions on the surface of ferrous metal substrates and prevent iron ionization. Its superior flash rust prevention performance greatly improves the salt spray resistance of water-based coatings.
[0069] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0070] In the following examples and comparative examples, the graphene oxide was purchased from Suzhou Hengqiu Technology Co., Ltd., China, with a purity of 95%, a thickness of 3.4-7 nm, a layer diameter of 10-50 μm, a layer number of 5-10, and a specific surface area of 100-300 m². 2 / g, sulfur content <5wt%. Titanium dioxide: rutile nano-titanium dioxide with an average particle size of 30nm.
[0071] Example 1
[0072] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0073] I. Preparation of waterborne modified epoxy resin dispersions:
[0074] Add 13g of bisphenol A type 903 epoxy resin, 8g of fatty acid (oleic acid), 2g of glycidyl methacrylate, and 6g of propylene glycol methyl ether to the reaction apparatus. Heat to 160℃ until the resin melts, then start stirring and heat to 200℃ for esterification for 2 hours. Take samples to measure the viscosity and acid value of the reaction system. When the acid value drops below 5, stop heating and immediately cool down. Once cooled to 130℃, transfer the reaction product to another reaction apparatus. Add 2g of hydrophilic hydroxymethylacrylamide to form a cross-linked structure. Add 5g of methyl methacrylate and 2g of... Styrene, 8g of ethylene glycol tert-butyl ether, and 1g of benzoyl peroxide were mixed and added to the above reaction system. The addition time was controlled at 3h, and then the reaction was kept at 130℃ for 2h. 8g of acrylic acid and 3g of ethylene glycol butyl ether were mixed to obtain an acrylic acid solution. The acrylic acid solution was added to the reaction system, and the addition time was controlled at 1h. After the addition was completed, the reaction was kept at 130℃ for 2h. After the reaction was completed, the mixture was cooled to room temperature. Then, dimethylethanolamine was added to the reaction system to adjust the pH to 7-8. Finally, deionized water was added to adjust the solid content to obtain a 45wt% waterborne modified epoxy resin dispersion.
[0075] II. Preparation of modified graphene / titanium dioxide materials:
[0076] 0.3 g of graphene oxide, 1 g of titanium dioxide, and 0.004 g of silane coupling agent KH550 were added to 150 ml of N,N-dimethylformamide and ultrasonically dispersed at 110 W for 1 h. Then, 20% (by weight) of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide was added and stirred at 300 rpm for 20 min. 0.1 g of L-histidine was dissolved in 50 ml of DMF to prepare an L-histidine solution. 50 ml of the L-histidine solution was added to the reaction system and stirred at 300 rpm and room temperature for 25 h. After the reaction, the pH of the reaction system was adjusted to 10. Then, tannic acid (tannic acid to graphene oxide mass ratio of 1:1) was added to the reaction system, and the temperature was raised to 80 °C and reacted at 300 rpm for 6 h. After the reaction, the mixture was cooled to room temperature, filtered, the precipitate was washed, and then freeze-dried to obtain the modified graphene / titanium dioxide material.
[0077] III. Preparation of Pigment Paste:
[0078] Add 12g of deionized water to a mixing container. While stirring at 500r / min, slowly add 3g of water-based wetting and dispersing agent (WinSperse 4000, WinSperse New Materials (Weifang) Co., Ltd.), 0.1g of water-based defoamer (water-based silicone defoamer, DIG-902W), and 0.2g of water-based wetting agent (silicone twin structure surfactant LAG-8000). Increase the stirring speed to 1000r / min and disperse at high speed for 5min. Reduce the stirring speed to 500r / min and add 3g of deionized water, 3g of zinc strontium phosphate anti-rust pigment (zinc strontium phosphate JP-B808), 8g of high-gloss barium sulfate, 2g of high-pigment carbon black, 1g of fumed nano silica, and 4g of modified graphene / titanium dioxide material. Increase the stirring speed to 1500r / min and disperse for 30min. Then, grind the mixture in a sand mill until the fineness is ≤10um. The result is qualified, and the color paste is obtained.
[0079] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0080] At a stirring speed of 500 r / min, 100 g of waterborne modified epoxy resin dispersion and the above color paste were mixed, and 1 g of dimethylethanolamine, 3 g of waterborne drying agent (YPWG-0160, Shanghai Kaiyin Chemical Co., Ltd.), 3 g of waterborne film-forming aid (DPNB, dipropylene glycol butyl ether), 0.2 g of waterborne coupling agent (waterborne silane coupling agent KH-911, Hangzhou Jessica Chemical Co., Ltd.), 1 g of waterborne anti-flash rust agent (HIF-3118 anti-flash rust agent, Yantai Hengxin Chemical Technology Co., Ltd.), and 1 g of waterborne polyurethane associative thickener (PU105A, Shanghai Jiahong Materials Technology Co., Ltd.) were added. The stirring speed was increased to 1200 r / min and dispersion was continued for 30 min to obtain an environmentally friendly, low-odor waterborne modified epoxy resin anti-corrosion coating.
[0081] Example 2
[0082] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0083] I. Preparation of waterborne modified epoxy resin dispersions:
[0084] The method is the same as in Example 1;
[0085] II. Preparation of modified graphene / titanium dioxide materials:
[0086] The method is the same as in Example 1;
[0087] III. Preparation of Pigment Paste:
[0088] Add 10g of deionized water to a mixing container, and then add 4g of aqueous wetting and dispersing agent (WinSperse) while stirring at 500 rpm. 4000 (Weibos New Materials (Weifang) Co., Ltd.), 0.1g of water-based defoamer (water-based organosilicon defoamer, DIG-902W), 0.3g of water-based wetting agent (organosilicon twin structure surfactant LAG-8000), then increase the speed to 1000r / min for high-speed dispersion for 5min, reduce the disperser speed to 500r / min, add 5g of deionized water, 4g of zinc strontium phosphate anti-rust pigment (zinc strontium phosphate JP-B808), 12g of high-gloss barium sulfate, 7g of 1250 mesh talc powder, 6g of iron oxide red (S110, Shanghai Yipin Pigment Co., Ltd.), 1g of fumed nano silica, 1g of polyamide wax (NEW-0401C, Nanjing Tianshi New Materials Technology Co., Ltd.), and 5g of modified graphene / titanium dioxide material, increase the speed to 1500r / min for dispersion for 30min, then place it in a sand mill and grind it to a fineness ≤15um, which is qualified, and the color paste is obtained;
[0089] IV. Preparation of Environmentally Friendly, Low-Odor Waterborne Acrylic-Modified Epoxy Resin Anticorrosive Coatings:
[0090] At a stirring speed of 500 r / min, the above-mentioned color paste and 100 g of water-based modified epoxy resin dispersion were mixed with 1.5 g of dimethylethanolamine, 4 g of water-based drier (YPWG-0160, Shanghai Kaiyin Chemical Co., Ltd.), 5 g of water-based film-forming aid (DPNB, dipropylene glycol butyl ether), 0.5 g of water-based coupling agent (water-based silane coupling agent KH-911, Hangzhou Jessica Chemical Co., Ltd.), 1 g of water-based anti-flash rust agent (HIF-3118 anti-flash rust agent, Yantai Hengxin Chemical Technology Co., Ltd.), and 1 g of water-based polyurethane associative thickener (PU105A, Shanghai Jiahong Materials Technology Co., Ltd.). The stirring speed was increased to 1200 r / min and the mixture was dispersed for 30 min to obtain an environmentally friendly, low-odor water-based acrylic modified epoxy resin anti-corrosion coating.
[0091] Example 3
[0092] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0093] I. Preparation of waterborne modified epoxy resin dispersions:
[0094] Same as Example 1
[0095] II. Preparation of modified graphene / titanium dioxide materials:
[0096] 0.4 g of graphene oxide, 1 g of titanium dioxide, and 0.006 g of silane coupling agent KH550 were added to 150 ml of N,N-dimethylformamide and ultrasonically dispersed at 110 W for 2 h. Then, 30% 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (by weight of graphene oxide) was added and stirred at 300 rpm for 30 min. 0.1 g of L-histidine was dissolved in 50 ml of DMF to prepare an L-histidine solution. 50 ml of the L-histidine solution was added to the reaction system and stirred at 300 rpm and room temperature for 25 h. After the reaction, the pH of the reaction system was adjusted to 10. Then, tannic acid (tannic acid to graphene oxide mass ratio of 1:2) was added to the reaction system, and the temperature was raised to 80 °C and reacted at 300 rpm for 6 h. After the reaction, the mixture was cooled to room temperature, filtered, the precipitate was washed, and then freeze-dried to obtain the modified graphene / titanium dioxide material.
[0097] III. Preparation of Pigment Paste:
[0098] Same as Example 1
[0099] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0100] Same as Example 1.
[0101] Example 4
[0102] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0103] I. Preparation of waterborne modified epoxy resin dispersions:
[0104] Add 13g of bisphenol A type 903 epoxy resin, 8g of fatty acid, 8g of glycidyl methacrylate, and 6g of propylene glycol methyl ether to the reaction apparatus. Heat to 160℃ until the resin melts, then start stirring and heat to 200℃. Maintain this temperature for esterification for 2 hours. Take samples to measure the viscosity and acid value of the reaction system. When the acid value drops below 5, stop heating and immediately cool down. Once the temperature drops to 130℃, transfer the reaction product to another reaction apparatus. Add 3g of hydrophilic hydroxymethylacrylamide to form a cross-linked structure. Add 5g of methyl methacrylate and 2g of styrene... 8g of ethylene glycol tert-butyl ether and 1g of benzoyl peroxide were mixed and added to the above reaction system. The addition time was controlled at 3h, and then the reaction was kept at 130℃ for 2h. 10g of acrylic acid and 3g of ethylene glycol butyl ether were mixed to obtain an acrylic acid solution. The acrylic acid solution was added to the reaction system and the addition time was controlled at 1h. After the addition was completed, the reaction was kept at 130℃ for 2h. After the reaction was completed, it was cooled to room temperature. Then, dimethylethanolamine was added to the reaction system to adjust the pH to 7-8. Finally, deionized water was added to adjust the solid content to obtain a 45wt% waterborne modified epoxy resin dispersion.
[0105] II. Preparation of modified graphene / titanium dioxide materials:
[0106] Same as Example 1
[0107] III. Preparation of Pigment Paste:
[0108] Same as Example 1
[0109] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0110] Same as Example 1.
[0111] Example 5
[0112] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0113] I. Preparation of waterborne modified epoxy resin dispersions:
[0114] Same as Example 1
[0115] II. Preparation of modified graphene / titanium dioxide materials:
[0116] Same as Example 1
[0117] III. Preparation of Pigment Paste:
[0118] Add 12g of deionized water to a mixing container. While stirring at 500r / min, slowly add 3g of aqueous wetting and dispersing agent (same as in Example 1), 0.1g of aqueous defoamer (same as in Example 1), and 0.2g of aqueous wetting agent (same as in Example 1). Increase the stirring speed to 1000r / min and disperse at high speed for 5min. Reduce the stirring speed to 500r / min and add 3g of deionized water, 3g of zinc strontium phosphate anti-rust pigment (same as in Example 1), 8g of high-gloss barium sulfate, 2g of high-pigment carbon black, 1g of fumed nano silica, and 8g of modified graphene / titanium dioxide material. Increase the stirring speed to 1500r / min and disperse for 30min. Then, place the mixture in a sand mill and grind it to a fineness ≤10um. The result is qualified, and the color paste is obtained.
[0119] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0120] Same as Example 1.
[0121] To better verify that the coating of this application has good performance, several comparative examples are given below for further explanation.
[0122] Comparative Example 1
[0123] Compared with Example 1, the difference is that glycidyl methacrylate was not added for modification in the preparation of the waterborne modified epoxy resin dispersion, while other conditions were the same as in Example 1.
[0124] Comparative Example 2
[0125] Compared with Example 1, the difference is that in the preparation of the waterborne modified epoxy resin dispersion, the acrylic monomer is replaced by an equal amount of methyl methacrylate, and the other conditions are the same as in Example 1.
[0126] Comparative Example 3
[0127] Compared with Example 1, the difference is that in the preparation of the waterborne modified epoxy resin dispersion, methyl methacrylate is replaced by an equal amount of acrylic acid monomer, and other conditions are the same as in Example 1.
[0128] Comparative Example 4
[0129] Compared with Example 1, the difference is that no silane coupling agent KH550 was added for pre-modification when preparing the modified graphene / titanium dioxide material, and the other conditions were the same as in Example 1.
[0130] Comparative Example 5
[0131] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0132] I. Preparation of waterborne modified epoxy resin dispersions:
[0133] Same as Example 1
[0134] II. Preparation of modified filler: 1.3g of graphene oxide and 0.004g of silane coupling agent were added to 150ml of N,N-dimethylformamide and ultrasonically dispersed at 110W for 1h. Then, 20% by weight of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide was added and stirred at 300rpm for 20min. 0.1g of L-histidine was dissolved in 50ml of DMF to prepare an L-histidine solution. 50ml of the L-histidine solution was added to the reaction system and stirred at 300rpm and room temperature for 25h. After the reaction, the pH of the reaction system was adjusted to 10. Then, tannic acid (tannic acid to graphene oxide mass ratio of 1:1) was added to the reaction system, and the temperature was raised to 80℃ and reacted at 300rpm for 6h. After the reaction, the temperature was cooled to room temperature, the reaction solution was filtered, the precipitate was washed, and then freeze-dried to obtain the modified filler.
[0135] III. Preparation of Pigment Paste:
[0136] The modified graphene / titanium dioxide material was replaced with an equal amount of modified filler, and other conditions were the same as in Example 1;
[0137] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0138] Same as Example 1.
[0139] Comparative Example 6
[0140] A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating includes the following steps:
[0141] I. Preparation of waterborne modified epoxy resin dispersions:
[0142] Same as Example 1
[0143] II. Preparation of modified fillers:
[0144] 0.3g of graphene oxide, 1g of titanium dioxide, and 0.004g of silane coupling agent were added to 150ml of N,N-dimethylformamide and ultrasonically dispersed at 110W for 1h. The pH of the reaction system was adjusted to 10. Then, tannic acid (tannic acid to graphene oxide mass ratio of 0.1:1) was added to the reaction system, and the temperature was raised to 80℃ and reacted at 300rpm for 6h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the precipitate was washed and freeze-dried to obtain the modified filler.
[0145] III. Preparation of Pigment Paste:
[0146] The modified graphene / titanium dioxide material was replaced with an equal amount of modified filler, and other conditions were the same as in Example 1;
[0147] IV. Preparation of environmentally friendly, low-odor water-based modified epoxy resin anti-corrosion coatings:
[0148] Same as Example 1.
[0149] The performance of the coatings prepared in the above embodiments and comparative examples was tested below. The test methods and test results are as follows.
[0150] The sample substrate used in the experiment was a 150mm×70mm×2mm tinplate. Before the experiment, the substrate needed surface treatment: first, the tinplate was sanded horizontally and vertically with sandpaper of appropriate coarseness; then, the sanded surface was wiped with xylene; finally, it was wiped clean with anhydrous ethanol and placed in a vacuum drying oven for later use. Before spraying, the air output of the spray gun was adjusted, the tinplate was placed in a fume hood, the fan and water curtain were turned on, and the distance between the spray gun and the tinplate was kept appropriate. Then, the coating was sprayed onto the sample substrate in an "S" shaped motion. The number of sprays for each sample was the same to ensure a consistent coating thickness, controlling the film thickness to around 30μm. After spraying, the samples were allowed to dry slightly before being placed in a ventilated area for further drying.
[0151] Test method:
[0152] Adhesion: Tested according to GB / T23257-2009 standard.
[0153] Salt spray resistance: Tested according to GB / T10125-1997 standard.
[0154] Water resistance: Tested according to GB / T5209-1985 standard.
[0155] Impact resistance test of coating: The test shall be conducted in accordance with GB / T 1732–2020 "Determination of Impact Resistance of Coating Film". The coating sample is placed flat on the impact testing machine and fixed in place. The weight is adjusted to a certain height on the slide (the weight fixing height is selected sequentially from low to high). The control button is pressed to let the weight fall freely and vertically. The coating sample is removed and the impact point is observed for cracks, fractures or even peeling. If no cracks, fractures or peeling are observed, the test is considered passed. Each sample is tested three times at each height. If all three tests pass, the test is considered passed.
[0156] The test results are shown in Table 1.
[0157] Table 1
[0158]
[0159]
[0160]
[0161] As can be seen from the test results in Table 1, this invention modifies epoxy resin with monomers such as glycidyl methacrylate, acrylic acid, and methyl methacrylate, introducing acrylate segments to improve the water resistance and corrosion resistance of the resin matrix. Moreover, the solvents and other additives used in this invention have low odor and low volatility, ensuring the environmental performance of the coating.
[0162] Compared to the comparative example, the modified graphene / titanium dioxide material added in this invention has a layered structure, which provides a certain degree of barrier properties. It can fill the microporous structure of the coating substrate and increase the diffusion path length of the corrosive medium through the coating substrate, thereby creating a labyrinth effect and improving the corrosion resistance of the coating. Furthermore, the L-histidine on the modified graphene / titanium dioxide material can act as a corrosion inhibitor, forming an oxide passivation layer with the substrate, thus better protecting the substrate.
[0163] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. A method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating, characterized in that, Includes the following steps: (1) Preparation of waterborne modified epoxy resin dispersion: Epoxy resin, fatty acid, and modified monomers are added to a first solvent and subjected to an esterification reaction at 200-250℃ for 1-2 hours. Then, a crosslinking agent is added at 120-140℃. Next, a mixture of acrylate monomers, styrene monomers, a second solvent, and an initiator is added to the reaction system, with a dropwise addition time of 2-4 hours. The reaction is then maintained at 120-140℃ for 1-2 hours. An acrylate monomer solution is added, and the reaction is maintained at 120-140℃ for another 1-2 hours. After the reaction is complete, an amine neutralizer is added for neutralization, and deionized water is added to adjust the solid content, yielding an aqueous modified epoxy resin dispersion. The modified monomer is glycidyl methacrylate. (2) Preparation of modified graphene / titanium dioxide materials: Graphene oxide, titanium dioxide, and silane coupling agent were added to N,N-dimethylformamide and ultrasonically dispersed until uniform. Then, 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC) was added and stirred to mix. L-histidine solution was then added and stirred to react. After the reaction was completed, the pH of the reaction system was adjusted. Tannic acid was then added to the reaction system and the temperature was raised to react. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the precipitate was washed and freeze-dried to obtain the modified graphene / titanium dioxide material. (3) Preparation of color paste: Add some deionized water to the mixing container, then add water-based wetting and dispersing agent, water-based defoamer, and water-based wetting agent under stirring conditions, and carry out one stirring and dispersion. Then add the remaining deionized water, modified graphene / titanium dioxide material, and pigments and fillers under stirring conditions, and carry out a second stirring and dispersion. Finally, grind the mixed slurry to obtain a color paste. (4) Preparation of anti-corrosion coatings: Add water-based modified epoxy resin dispersion to a mixing container, and under stirring conditions add amine neutralizer, water-based drier, water-based coupling agent, water-based film-forming aid, color paste, water-based flash rust inhibitor, and water-based thickener, and stir and disperse to obtain an environmentally friendly, low-odor water-based acrylic modified epoxy resin anti-corrosion coating.
2. The preparation method of the environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (1), the epoxy resin is a bisphenol A type epoxy resin; and / or the first solvent and the second solvent are one or a mixture of two of propylene glycol methyl ether and ethylene glycol tert-butyl ether; and / or the crosslinking agent is hydroxymethylacrylamide; and / or the acrylate monomer is methyl methacrylate; and / or the initiator is benzoyl peroxide; and / or the acrylate monomer is acrylic acid; and / or the amine neutralizing agent is dimethylethanolamine.
3. The preparation method of the environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (1), the amounts of epoxy resin, fatty acid, first solvent, crosslinking agent, acrylate monomer, styrene monomer, second solvent, initiator, acrylate monomer solution, and amine neutralizer are 10-15 wt%, 8-10 wt%, 5-8 wt%, 1-3 wt%, 5-8 wt%, 1-5 wt%, 7-10 wt%, 0.5-1.5 wt%, 11-15 wt%, and 1-3 wt% of the mass of the waterborne modified epoxy resin dispersion, respectively; the solid content of the waterborne modified epoxy resin dispersion is 45-48 wt%.
4. The preparation method of the environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (2), the mass ratio of graphene oxide, titanium dioxide, and silane coupling agent is (0.3-0.5):1:(0.003-0.006); and / or the ultrasonic power of the ultrasonic dispersion is 100-150W, and the ultrasonic time is 1-2h; and / or the amount of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide added is 20-30% of the mass of graphene oxide; the stirring speed during stirring and mixing is 300-500rpm, and the stirring and mixing time is 20-30min.
5. The preparation method of an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (2), the amount of L-histidine added is 20-30% of the mass of graphene oxide; and / or the temperature of the stirring reaction is room temperature, the stirring speed is 200-500 rpm, and the time is 20-30 h.
6. The method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (2), the pH of the reaction system is adjusted to 10, the mass ratio of tannic acid to graphene oxide is 1:(1-2), the temperature of the reaction is raised to 75-85℃, the stirring speed during the reaction is 200-500rpm, and the reaction time is 5-7h.
7. The method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (3), the pigment and filler are a mixture of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, and fumed nano silica, and the mass ratio of the zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, high-pigment carbon black, and fumed nano silica is (3-5):(8-10):(2-3):(1-2); or the pigment and filler are a mixture of zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, fumed nano silica, talc, iron oxide red, and polyamide wax; the mass ratio of the zinc strontium phosphate anti-rust pigment, high-gloss barium sulfate, talc, iron oxide red, fumed nano silica, and polyamide wax is (3-5):(10-15):(5-10):(5-7):(1-2):(1-2).
8. The method for preparing an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (3), the amounts of deionized water, waterborne defoamer, waterborne wetting and dispersing agent, waterborne wetting agent, pigments and fillers, and modified graphene / titanium dioxide material are 12-15 wt%, 0.1-0.2 wt%, 3-5 wt%, 0.2-0.5 wt%, 10-45 wt%, and 4-8 wt% of the mass of the waterborne modified epoxy resin dispersion, respectively.
9. The preparation method of an environmentally friendly, low-odor waterborne acrylic-modified epoxy resin anticorrosive coating according to claim 1, characterized in that, In step (4), the amount of waterborne modified epoxy resin dispersion added is 40-70 wt% of the total amount of environmentally friendly, low-odor waterborne acrylic modified epoxy resin anti-corrosion coating. The amounts of amine neutralizer, waterborne drying agent, waterborne film-forming aid, waterborne coupling agent, waterborne flash rust inhibitor, and waterborne thickener are 1-5 wt%, 3-5 wt%, 3-6 wt%, 0.2-2 wt%, 1-3 wt%, and 1-2 wt% of the mass of waterborne modified epoxy resin dispersion, respectively.
Citation Information
Patent Citations
Water-borne anti-corrosive coating for automobile accessories and preparation method thereof
CN107216802A
Preparation method for low acid value and low VOC waterborne acrylic acid and fatty acid modified epoxy resin
CN104513343A
Graphene-containing self-repairing epoxy silver colloid
CN108276929A
Anticorrosive filler containing two-dimensional nanosheet-point structure rust conversion, preparation method and application
CN117645811A